Impact of the EU deep and comprehensive free trade area agreements on trade performance of Georgia and Moldova - Emir Eteria (CES Working Papers, 2020)
The paper aims to analyse the effects in the trade performance of Georgia and Moldova in light of the Deep and Comprehensive Free Trade Area (DCFTA) agreements with the EU. Hence, data for the period 2010-2019 is analysed to reveal the latest developments in the trade performance of these countries. The conducted analysis points to some positive developments in the trade of Georgia and Moldova with the EU for 2015-2019, however, compared to 2010-2014 or pre-DCFTA period the average annual growth rate of exports of both countries declined. Moreover, Georgia's success to increase exports to the EU remain relatively modest as compared to Moldova. Therefore, Moldova has achieved more deep trade integration with the EU than Georgia. Furthermore, the effect of DCFTAs on trade relations between Georgia and Moldova is not substantial, and therefore, increased economic integration between the EU associated countries is not yet evident.
Keywords: 330; Deep and Comprehensive Free Trade Area; Trade Performance; Georgia; Moldova; EU